Original Short Stories $1 (BVolume 02s - Maupassant, Guy de, 1850-1893; Henderson, A. E.; McMaster, Albert Cohn; Quesada, Louise Charlotte Garstin (Salt Lake City, UT : Project Gutenberg, 2004)
"Original Short Stories $1 (BVolume 02" by Guy de Maupassant is a collection of short stories written during the late 19th century. This volume includes various tales, each depicting human emotions and experiences, often set against the backdrop of contemporary French society. The stories range from romantic entanglements to existential musings, showcasing Maupassant's keen observation of character and social dynamics. At the start of this volume, the first story, "The Colonel's Ideas," introduces Colonel Laporte, who muses about the passionate nature of French men and their undying infatuation with women, even in the most trying circumstances. The narrative shifts to an anecdote from the Franco-Prussian War, where the colonel recounts a harrowing retreat indicative of soldierly bravery intertwined with a longing for feminine connection. The colonel$1 (Bs reflections highlight themes of love, duty, and courage, setting the stage for the richly layered storytelling found throughout this collection. (This is an automatically generated summary.)s
The colonel's ideas -- Mother Sauvage -- Epiphany -- The mustache -- Madame Baptiste -- The question of Latin -- A meeting -- The blind man -- Indiscretion -- A family affair -- Beside Schopenhauer's corpse.
Release date is 2004-10-03
Produced by David Widger
Keywords: Short stories, French -- Translations into English